Newly Homeless Youth Typically Return Home - Milburn, Norweeta G. (2007)
165 newly homeless adolescents from Melbourne, Australia and 261 from Los Angeles, United States were surveyed and followed for two years. Most newly homeless adolescents returned home (70% U.S., 47% Australia) for significant amounts of time (39% U.S., 17% Australia more than 12 months) within two years of becoming homeless.